Tinnitus-associated cognitive and psychological impairments: a comprehensive review meta-analysis - Yang, Dong; Zhang, Dan; Zhang, Xinmiao; Li, Xin (Frontiers in Neuroscience, 2024)
Background: Tinnitus is strongly associated with an increased risk of cognitive disabilitiesorders. This review meta-analysis first time explored the association of tinnitus with inducement and development of cognitive disorders, including Alzheimer's disease, altered learning and auditory attention-deficit/hyperactivity disorder (ADHD), depression, anxiety and poor sleep qualityinsomnia. The findings of this research will provide valuable support for future investigations aimed at determining the correlation between tinnitus and the risk of cognitive impairments, particularly Alzheimer's disease.Objectives: We investigated the potential correlation between tinnitus and the risk of various cognitive impairmentsdisorders, such as dementiaAlzheimer's disease, compromised learning attentionADHD, anxiety, depression, and insomnia. The study examined this relationship collectively and by categorizing the data based on different age groups.